Theoretical aspects of export development promotion by the state - Radzhabov, M.M., Radzhabova, O.R.,; Gulmagomedova, T.G., Osmanov, G.A.,; Tagirov A., Aygumov, A.G., (Opción, 2019)
This paper discusses the condition and problems of state incentives for export development via comparative qualitative research methods. As a result, export promotion is one of the most important policies of the world’s countries. For this purpose, various methods are used aimed at supporting businessmen abroad and promoting their goods on world markets. In conclusion, state support for export activities and export-oriented industries is one of the priority goals of national and economic policies and components of the development of the national economy.